2022
DOI: 10.1093/ofid/ofac140
|View full text |Cite
|
Sign up to set email alerts
|

A Desirability of Outcome Ranking Analysis of a Randomized Clinical Trial Comparing Seven Versus Fourteen Days of Antibiotics for Uncomplicated Gram-Negative Bloodstream Infection

Abstract: Background Although a short course (7 days) of antibiotics has been demonstrated to be non-inferior to a conventional course (14 days) in terms of mortality and infectious complications for patients with a Gram-negative bacterial bloodstream infection (GNB), it is unknown whether a shorter treatment duration can provide a better overall clinical outcome. Methods We applied a bloodstream infection-specific desirability of outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Given the limited data for shorter durations of therapy when oral BLs are used, the 14-day duration of therapy used in our study may still be clinically applicable. In addition of total treatment duration, the average duration of IV therapy was comparable to other studies at approximately 5 days [17][18][19][20][21][22][23]28,30]. It is important to note that IV duration in our study was on average one day shorter in the FQ group (4 days vs. 5 days).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Given the limited data for shorter durations of therapy when oral BLs are used, the 14-day duration of therapy used in our study may still be clinically applicable. In addition of total treatment duration, the average duration of IV therapy was comparable to other studies at approximately 5 days [17][18][19][20][21][22][23]28,30]. It is important to note that IV duration in our study was on average one day shorter in the FQ group (4 days vs. 5 days).…”
Section: Discussionsupporting
confidence: 83%
“…However, oral BLs were underrepresented in this study (< 20% of overall cohort), which limits the ability to apply these findings when oral BLs are used as stepdown therapy. A desirability of outcome ranking (DOOR) analysis including this study suggests that short course (7 days) of antibiotics has comparable clinical outcomes to conventional course (14 days) in this patient population [30]. Given the limited data for shorter durations of therapy when oral BLs are used, the 14-day duration of therapy used in our study may still be clinically applicable.…”
Section: Discussionmentioning
confidence: 88%
“…Limitations of this study included minimal minority representation and lack of a pre-CDI-antibiotic stool specimen, which inhibited a full assessment of SER-109’s effect on the microbiome. Overall, this study showed SER-109 was superior in reducing CDI recurrence vs placebo and is a promising start for this new drug class in decreasing CDI burden in the US. Howard-Anderson J et al A Desirability of Outcome Ranking Analysis of Randomized Clinical Trial Comparing Seven vs Fourteen Days of Antibiotics for Uncomplicated Gram-Negative Bloodstream Infection 17 …”
Section: Introductionmentioning
confidence: 80%
“…The top 10 general ID and top 1 HIV/AIDS papers are summarized here in alphabetical order of the first author. 16-39 Chuang YC et al The combination of daptomycin with β-lactam antibiotics is more effective than daptomycin alone for vancomycin-resistant Enterococcus faecium bloodstream infection 25 …”
Section: Introductionmentioning
confidence: 99%
“…Many others have applied DOOR analysis retrospectively to previously performed clinical trials. [35][36][37][38] These analyses must work within the framework of data collected as part of the original trial and may be limited, especially in ability to measure patient-reported outcomes.…”
Section: Approaches To Build and Apply Doormentioning
confidence: 99%